Oropharyngeal botryomycosis in a geriatric mare. (27th June 2017) - Merchan, A.; Jose‐Cunilleras, E.; Prades, M.; Ribera, T.; Viu, J.; Rodríguez‐Pozo, M. L.; Ramis, A. J.
Summary: Botryomycosis is an uncommon chronic bacterial infection that can have cutaneous and visceral involvement. This report describes an 18‐year‐old mixed‐breed mare presented with dysphagia, dyspnoea and an upper respiratory noise that developed secondary to oropharyngeal botryomycosis. Histological examination of the mass showed a granulomatous formation with Splendore–Hoeppli phenomenon surrounding Gram‐positive bacteria. This report describes the clinical signs, approach and management of an oropharyngeal Staphylococcus aureus granuloma in a geriatric mare.